Tooth Crown Morphology in Turner and Klinefelter Syndrome Individuals from a Croatian Sample - Christopher Maier; Jelena Dumančić; Hrvoje Brkić; Zvonimir Kaić; Ivana Savić Pavičin; Zvonko Poje; G. Richard Scott (Acta Stomatologica Croatica, 2019)
Objective: Turner syndrome (TS) and Klinefelter syndrome (KS) represent the two most common X chromosome aneuploidies, each associated with systemic disruptions to growth and development. Effects of these conditions on tooth crown morphology are explored in a sample of Croatian individuals. Material and Methods: The sample included 57 TS, 37 KS and 88 control individuals. Dental crown morphology was scored on dental casts according to the Turner-Scott Dental Anthropology System. Results: Incisor shoveling and the hypocone were significantly different between TS individuals and both control and KS individuals. Individuals with TS exhibit lower grades of expression than either group. Furthermore, the number of lingual cusps on the mandibular premolars, the hypoconulid on the mandibular second molar, and cusp 7 on the mandibular first molar were significantly different, though pair-wise comparisons did not elucidate these differences. Tuberculum dentale, distal accessory ridge, and Carabelli’s trait were expressed similarly to the control. KS individuals were not significantly different from control individuals for any trait, though this may be related to sample size. Conclusions: Previous studies suggest the loss of an X chromosome has a reducing effect on dental crown morphology, which is confirmed in this research. TS individuals exhibit generally simpler dental morphology compared to the control sample, though some traits are expressed comparably to the control sample. The effects of KS are less clear. Though previous studies suggest that the presence of an extra X chromosome increases dental crown dimensions, there was no notable effect on crown morphology in this study.